Pengaruh Edukasi Peran Keluarga Terhadap Dukungan Keluarga Dalam Kemampuan Merawat Pasien Diabetes Melitus Pada Pasien Poliklinik Di Rs Hermina Depok Tahun 2023 - Bayaranie, Meidyana; Yuliza, Emi; Herliana, Irma (Barongko: Jurnal Ilmu Kesehatan, 2024)
The prevalence of diabetes mellitus (DM) continues to increase globally and is projected to triple by 2030. Diabetes Mellitus (DM) is a chronic disease that requires effective self-management, according to Perkani. The inability of families to understand and recognize their crucial role in caring for DM patients can have serious consequences on the patients' well-being. This study aims to determine the effect of family role education on family support in the ability to care for diabetes mellitus patients. The research design is a quantitative study adopting a Quasi-Experimental method with a Non-Randomized Without Control Group Pretest and Posttest Design approach. The population comprises diabetes patients using the outpatient services at Hermina Hospital Depok in May, with a purposive sampling technique involving 25 respondents. The results indicate that the distribution of family support before the education showed 76% in the unsupportive category, and after the education, it increased to 84%. The Paired Sample T-Test significance was 0.000, which is less than 0.05. Thus, this study shows that family role education has a significant effect on family support in the ability to care for diabetes mellitus patients.